EKSPLORASI FUNGI INDIGENUS PENGHASIL ENZIM LAKASE PADA LIMBAH BATIK PEKALONGAN - UUN ROHMAWATI (Universitas Nahdlatul Ulama Pasuruan, 2024)
Pekalongan is one of the largest batik producing cities in Indonesia. In general, batik industry waste is directly disposed of into the environment, causing pollution and being hazardous to health. One alternative is to utilize local fungi (indigenous) because they produce laccase enzymes that can decompose dyes. The purpose of this study was to isolate and select fungi producing laccase enzymes from the environment contaminated with batik waste in Pekalongan. The methods used were qualitative screening using tannic acid, laccase enzyme activity testing, and macroscopic and microscopic observations. The results of this study obtained 127 fungal isolates, but only 27 fungal isolates formed yellow to brown zones during qualitative screening. In the laccase enzyme activity test, 21 fungal isolates were obtained that could produce laccase enzyme activity. Five potential fungi producing the highest laccase enzyme activity were taken, namely isolates KByT1, 33ByL1, B BrT1, 58 JL2, and 13 ByL1 (laccase enzyme activity in sequence, namely 19.82 U/ml, 6.08 U/mL, 5.98 U/mL, 3.89 U/mL and 3.79 U/mL). Isolates KByT1 and B BrT1 belong to the genus Trichoderma, isolate 33ByL1 belongs to the genus Talaromyces, isolate 58 JL2 belongs to the genus Fusarium and isolate 13 ByL1 belongs to the genus Aspergillus.